Examining the Turkish men's professional basketball team's success according to game-related statistics with discriminant analysis - Dogan, I.; Isik, Ö.; Ersöz, Y. (International Journal of Performance Analysis in Sport, 2016)
The aim of this study was to investigate the game-related statistics that discriminate between teams according to their league position in the Turkish Basketball League. Data were collected from the official box scores for 16 participated teams during the 2014-2015 regular season of the Turkish Basketball League. Teams were divided into two groups according to their league position; top 8 teams were called the top half teams and other 8 teams were called the bottom half teams. Players who played for less than one-quarter of the season or less than half a game period were omitted from the sample. The final data set obtained from 198 basketball players. The recorded game-related statistics were standardized according to a player's time on court. Independent samples t-tests were used to compare descriptive results from the game-related statistics. Also, discriminant analysis was applied to discover the statistical team variables that better discriminated between the two types of team. The mean differences between teams that were found to be statistically significant were assists, steals, defensive rebounds, turnovers and offensive rebounds. In the 2014-2015 regular season of Turkish Basketball League assists, steals, defensive rebounds, turnovers and offensive rebounds were the variables that had a major contribution to a team success. As a result, it was found that offensive rebounds, defensive rebounds, assists, steals and turnovers were more important game-related statistics than others. These results suggest that defense is more effective for team success than offense.